2020
DOI: 10.1007/s42452-020-03690-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced chromatographic technique for performance simulation of anti-Alzheimer agent: an ensemble machine learning approach

Abstract: This work employs the application of three artificial intelligence (AI) techniques namely; support vector machine (SVM), Hammerstein-Wiener (HW) and multi-layer perceptron (MLP) for predicting the qualitative properties of an anti-Alzheimer agent using high-pressure liquid chromatography technique. The mobile phase (inform of acetonitrile and trifluoroacetic acid) and the column temperature was used as the predictors in modelling the maximum retention time (tR-max) and resolution (Resol.) as the output variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In this section, the obtained results are shown both quantitatively and in a visualized form. Table 1 demonstrates the correlation analysis of the variables involved in the study (Ghali et al 2020), namely, number of abdominal writhes, number mean reaction time of paw licking and paw oedema diameter. Acetic acid-induced abdominal writhes result from the stimulation of the release of arachidonic acid to form PG that plays a critical role in pain mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, the obtained results are shown both quantitatively and in a visualized form. Table 1 demonstrates the correlation analysis of the variables involved in the study (Ghali et al 2020), namely, number of abdominal writhes, number mean reaction time of paw licking and paw oedema diameter. Acetic acid-induced abdominal writhes result from the stimulation of the release of arachidonic acid to form PG that plays a critical role in pain mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Social distancing and limitation of public and economic activities showed direct impact to the financial capability and resilience in multiple countries including studies here in Northern Cyprus. Even though many studies have stated that the using of technology, with its mobility and personalized benefits, helped lecturers promoting innovation in education, not just limited to the improvement of lecture-style teaching, but also through more humanistic approach in direct open discussion and a more controlled systematic information collection as shown in a study made in Indonesia (17). Our study results showed that out of 209 participant's shows 64.6% of participants had minimal to mild anxiety while 34.6% had moderate to severe anxiety in accordance with the generalized anxiety disorder -7 (GAD-7) scale.…”
Section: Discussionmentioning
confidence: 99%
“…Panic disorder (sensitivity 74%, specificity 81%), social anxiety disorder (sensitivity 72%, specificity 80%), and post-traumatic stress disorder (sensitivity 66%, specificity 81%) are all quite well-screened disorders. (17).…”
Section: Study Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of this research, the employed data‐driven intelligence, ANN, ANFIS, MLR models, and novel ensemble techniques, and a brief description of the mathematical concept for each of these models as well as the related citations and equations are provided in the Supporting Information Appendix (A1–A4) in more detail [28‐35].…”
Section: Methodsmentioning
confidence: 99%